Obesity prevalence from a European perspective: a systematic review - Berghöfer, Anne; Pischon, Tobias; Reinhold, Thomas; Apovian, Caroline M; Sharma, Arya M; Willich, Stefan N (BMC public health, 2008)
Background Obesity has been recognised as an important contributing factor in the development of various diseases, but comparative data on this condition are limited. We therefore aimed to identify and discuss current epidemiological data on the prevalence of obesity in European countries. Methods We identified relevant published studies by means of a MEDLINE search (1990–2008) supplemented by information obtained from regulatory agencies. We only included surveys that used direct measures of weight and height and were representative of each country's overall population. Results In Europe, the prevalence of obesity (body mass index ≥ 30 kg/m 2 ) in men ranged from 4.0% to 28.3% and in women from 6.2% to 36.5%. We observed considerable geographic variation, with prevalence rates in Central, Eastern, and Southern Europe being higher than those in Western and Northern Europe. Conclusion In Europe, obesity has reached epidemic proportions. The data presented in our review emphasise the need for effective therapeutic and preventive strategies.